Role of family accommodation of child symptoms, parenting style and parental stress in Prediction of anxiety disorder in 6 - 10 years old children in Northern Iran - Majid Zamani; Mohsen Jalali; Elnaz Pourahmadi (مجله دانشگاه علوم پزشکی گرگان, 2019)
Background and Objective: Childhood behavioral and emotional problems may be continus to puberty, even extend to elderly. This study was carried out to determine the role of family accommodation of child symptoms, parenting style and parental stress in prediction of anxiety disorder in children with 6 - 10 years old in Golestan province, north of Iran.